Search for neutral MSSM Higgs bosons decaying to tau(+)tau(-) pairs in proton-proton collisions root s=7 TeV with the ATLAS detector - Onofre, A. (2011)
A search for neutral Higgs bosons decaying to pairs of τ leptons with the ATLAS detector at the LHC is presented. The analysis is based on proton–proton collisions at a center-of-mass energy of 7 TeV, recorded in 2010 and corresponding to an integrated luminosity of 36 pb−1. After signal selection, 276 events are observed in this data sample. The observed number of events is consistent with the total expected background of 269±36269±36 events. Exclusion limits at the 95% confidence level are derived for the production cross section of a generic Higgs boson ϕ as a function of the Higgs boson mass and for A/H/hA/H/h production in the Minimal Supersymmetric Standard Model (MSSM) as a function of the parameters mAmA and View the MathML sourcetanβ.